Self-efficacy in Online Learning: A Bibliometric Analysis - Onwardono Rit Riyanto; Ilham Muhammad; Nurul Husnah Mustika Sari; Nabil Husnan Azmy (MASI Mandiri Edukasi, 2025)
Whether synchronous or asynchronous, online learning utilizes various digital tools that significantly differentiate it from conventional offline learning. One critical factor influencing students' success in this environment is self-efficacy, which reflects their belief in their ability to perform learning tasks effectively. Despite increasing research on online learning self-efficacy, a comprehensive overview of its development and trends is needed. This study aims to analyze the research landscape related to online learning self-efficacy over the last five years, identifying key contributors, collaboration networks, and thematic research focuses. This study employs descriptive bibliometric analysis to systematically examine the growth, distribution, and impact of research in this field. Data was collected from major academic databases, focusing on publications between 2018 and 2023. Key parameters analyzed include publication trends, country-wise research output, institutional contributions, collaboration networks, keyword co-occurrence, and citation impact. Findings indicate a growing interest in online learning self-efficacy studies, particularly between 2018 and 2021. The United Kingdom leads in publications, while United States researchers engage in the most international collaborations. The Hong Kong Polytechnic University emerges as the top institution in this field. Most studies appear in education and technology journals, with commonly associated keywords including motivation, e-learning, self-concept, and self-regulated learning. Quantitative research dominates, as 84 of the 100 most-cited publications employ quantitative methodologies, with students as the most frequently studied sample group. These findings provide insights into scholarly trends, highlighting key contributors and research directions for future studies.